Problems of assessing the oil and gas potential of the north-eastern part of the Ukrainian sector of the Black Sea - O. M. Rusakov; R.I. Kutas (Геофизический журнал, 2011)
For the first time oil and gas perspectives have been evaluated for the NE Ukrainian sector in the Black Sea applying a world -wide acknowledged methodology whose coherent constituents are modelling thermal regime of a basin, taking into account of a kerogen type and analyzing migration paths. It has been demonstrated that the Maykop series cannot provide with sufficient hydrocarbon potential. However, there are favourable conditions in this region for replenishing and accumulating hydrocarbons due to their migrating from deeper sources, including the upper mantle. To evaluate this oil and gas potential it is necessary to perform geological exploration in the zone of gas seeps as well as laboratory studying isotopic composition of carbon and hydrogen in methane.